Limited Range-Filling Among Endemic Forest Herbs of Eastern North America and Its Implications for Conservation With Climate Change - Erlandson, Stephanie K.; Bellemare, Jesse; Moeller, David A. (Frontiers in Ecology and Evolution, 2021)
Biodiversity hotspots host a high diversity of narrowly-distributed endemic species, which are increasingly threatened by climate change. In eastern North America, the highest concentration of plant diversity and endemism occurs in the Southern Appalachian Mountains (SAM). It has been hypothesized that this region served as a refugium during Pleistocene glacial cycles and that postglacial migration northward was dispersal limited. We tested this hypothesis using species distribution models for eight forest herb species. We also quantified the extent to which the geography of suitable habitat shifted away from the current range. We developed species distribution models for four forest herb species endemic to the SAM and four that co-occur in the same SAM habitats but have broader ranges. For widespread species, we built models using (1) all occurrences and (2) only those that overlap the SAM hotspot in order to evaluate the potential for models to predict suitable habitat beyond the SAM. We evaluated the extent to which predicted climatically-suitable areas are projected to shift away from their current ranges under current and future climate change. We detected unoccupied but suitable habitat in regions up to 1100 km north of the endemic species’ ranges. Endemic ranges are disjunct from suitable northern areas due to a ~100-150 km gap of unsuitable habitat. Under future climate change, models predicted severe reductions in predicted suitable habitat within current endemic ranges. For nonendemic species, we found similar overall patterns and gap of unsuitability in the same geographic location. Our results suggest a history of dispersal limitation following the last glacial maximum along with an environmental barrier to northward migration. Conservation of endemic species would likely require intervention and assisted migration to suitable habitat in northern New England and Canada.